2018
DOI: 10.3390/nu10081021
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Natural Products and Their Bioactive Compounds Inducing ER Stress-Mediated Apoptosis: A Review

Abstract: Cancer is the second biggest cause of death worldwide. Despite a number of studies being conducted, the effective mechanism for treating cancer has not yet been fully understood. The tumor-microenvironment such as hypoxia, low nutrients could disturb function of endoplasmic reticulum (ER) to maintain cellular homeostasis, ultimately leading to the accumulation of unfolded proteins in ER, so-called ER stress. The ER stress has a close relation with cancer. ER stress initiates unfolded protein response (UPR) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
297
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(302 citation statements)
references
References 175 publications
3
297
0
2
Order By: Relevance
“…Here, in our PEL‐induced CDI model, we demonstrated that in secretory AVP neurons, ER stress may also initiate apoptosis, in agreement with evidence found in other issues. ER stress was reported to be regulated by three canonical signaling pathways: PERK‐eIF2α‐ATF4‐CHOP, IRE1‐XBP1, and ATF6‐ERAD, in various issues . Further, several studies have reported that the PERK‐eIF2α‐ATF4‐CHOP signaling pathway plays an essential role in ER stress‐induced apoptosis, especially in neuronal issues including spinal cord injury, subarachnoid hemorrhage injury, and cerebral ischemia injury .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, in our PEL‐induced CDI model, we demonstrated that in secretory AVP neurons, ER stress may also initiate apoptosis, in agreement with evidence found in other issues. ER stress was reported to be regulated by three canonical signaling pathways: PERK‐eIF2α‐ATF4‐CHOP, IRE1‐XBP1, and ATF6‐ERAD, in various issues . Further, several studies have reported that the PERK‐eIF2α‐ATF4‐CHOP signaling pathway plays an essential role in ER stress‐induced apoptosis, especially in neuronal issues including spinal cord injury, subarachnoid hemorrhage injury, and cerebral ischemia injury .…”
Section: Discussionmentioning
confidence: 99%
“…ER stress was reported to be regulated by three canonical signaling pathways: PERK-eIF2α-ATF4-CHOP, IRE1-XBP1, and ATF6-ERAD, in various issues. 34 Further, several studies have reported that the PERK-eIF2α-ATF4-CHOP signaling pathway plays an essential role in ER stress-induced apoptosis, especially in neuronal issues including spinal cord injury, subarachnoid hemorrhage injury, and cerebral ischemia injury. 35,36 In the present study, our data indicated consistent involvement of PERK-eIF2α-ATF4-CHOP in ER stress-induced apoptosis in CDI generated by PEL surgery.…”
Section: Involvement Of Er Stress In Neuronal Apoptosismentioning
confidence: 99%
“…Thus, finding more candidate drugs for tumour/cancer treatment are of importance. It is reported that half of the current used drugs are derived from the natural agents, and natural components from plants are potential resource for finding effective candidate drugs with low toxicity, and increasing antitumour/cancer researches have suggested that natural compounds are feasible way for finding new antitumour/cancer candidate drugs in the future …”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…It is reported that half of the current used drugs are derived from the natural agents, and natural components from plants are potential resource for finding effective candidate drugs with low toxicity, [95] and increasing antitumour/cancer researches have suggested that natural compounds are feasible way for finding new antitumour/cancer candidate drugs in the future. [96,97] Paeonia lactiflora, an important TCM, has a long history to widely use in the management of various tumours and inflammatory diseases in China. Modern studies have found that peony and its prescription have good pharmacological effects in the treatment of breast cancer, rheumatoid arthritis, ulcerative colitis and other diseases.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…4 ER stress-mediated cell apoptosis signalling is activated if the UPR fails to correct misfolded proteins in the ER. 6 However, the mechanisms of ER stress-mediated cell apoptosis remain obscure, and there is far too little distinction regarding which specific effectors of death dominate in specific cellular environment. Furthermore, increasing researches have suggested a role of ER stress-mediated apoptosis in the physiopathology of manganism.…”
mentioning
confidence: 99%